The hidden shrines of Singapore : mapping and narrating multi-religious heritages - Liu, Bryan Jihao (2019)
The Hidden Shrines of Singapore is a digital humanities research project that aims to document and explore different shrines in Singapore with the use of augmented reality. Additionally, due to the success of documenting shrines in Singapore, we have included shrines from Sri Lanka as well. This project will comprise of two parts, the website and android application. The website is used as repository to crowdsource information and images about shrines. It achieves that by allowing users to upload images of shrine and its details. Through the website, staff (user with administrative rights) will be able to approve or reject shrine application. On the other hand, the android application allows user to download shrines for offline use. The shrines can be downloaded with the use of clustering algorithms. Once the shrine is downloaded, users will be able to utilise augmented reality to explore and discover shrines in Singapore. Using the augmented reality feature, they can detect images of shrine and pull out its relevant information from the database. The information that is pulled out, can be in the form of text or video. In addition, user will be able to favourite shrines that they are interested in and save it to a watchlist for viewing later. Moreover, the app also provides a convenient way to search for the nearest shrine to user’s location. The planning, development and technology used in this system are detailed within this report.